2024
DOI: 10.1007/s11684-024-1055-9
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-dependent phenylacetylglutamine in cardiovascular disease: current knowledge and new insights

Yaonan Song,
Haoran Wei,
Zhitong Zhou
et al.

Abstract: Phenylacetylglutamine (PAGln) is an amino acid derivate that comes from the amino acid phenylalanine. There are increasing studies showing that the level of PAGln is associated with the risk of different cardiovascular diseases. In this review, we discussed the metabolic pathway of PAGln production and the quantitative measurement methods of PAGln. We summarized the epidemiological evidence to show the role of PAGln in diagnostic and prognostic value in several cardiovascular diseases, such as heart failure, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…In the Song Y. et al experimental study it was suggested that AAAs derivates can activate platelets and mediate thrombosis via adrenergic receptor activation. Their production is connected with gut microbiota composition via a rise of pathogenic strains, such as Streptococcus spp., Enterococcus spp., and Ruminococcus spp., which can induce AF via an increase of trimethylamine-N-oxide, indole sulfate, and primary bile acids circulation [33]. The topic of thrombosis-associated metabolomics is understudied, and has a big potential for new biomarkers identification.…”
Section: Discussionmentioning
confidence: 99%
“…In the Song Y. et al experimental study it was suggested that AAAs derivates can activate platelets and mediate thrombosis via adrenergic receptor activation. Their production is connected with gut microbiota composition via a rise of pathogenic strains, such as Streptococcus spp., Enterococcus spp., and Ruminococcus spp., which can induce AF via an increase of trimethylamine-N-oxide, indole sulfate, and primary bile acids circulation [33]. The topic of thrombosis-associated metabolomics is understudied, and has a big potential for new biomarkers identification.…”
Section: Discussionmentioning
confidence: 99%